Mechanisms of antixenosis, antibiosis, and tolerance of fourteen soybean genotypes in response to whiteflies (Bemisia tabaci) - APRI SULISTYO; ALFI INAYATI (Society for Indonesian Biodiversity, 2016)
Sulistyo A, Inayati A. 2016. Mechanisms of antixenosis, antibiosis, and tolerance of fourteen soybean genotypes in response to whiteflies (Bemisia tabaci). Biodiversitas 17: 447-453. The attack of whiteflies (Bemisia tabaci) in soybean cultivation in Indonesia is one of the limiting factors in increasing the national soybean production. Planting resistant varieties could reduce yield losses due to the damage caused by these pests. This study was conducted to evaluate the resistance of 14 soybean genotypes to the whiteflies. A free- choice and no-choice test was conducted in a green house to study the antixenosis and antibiosis. Meanwhile, field evaluation was conducted to determine the tolerance of soybean genotypes to the whiteflies. Determination of the resistance of soybean genotypes to whiteflies based on the intensity of leaf damage that occurs on fifth weeks after infestation. The results showed that in free-choice test, Gema, IAC-100/Kaba-6, Malabar/IAC-100-85, Kaba/IAC-100//Burangrang-60, and Kaba/IAC-100//Burangrang-63 showed antixenosis mechanism which correlates with length and low density of leaf trichomes as well as leaf thickness. In the no-choice test, antibiosis mechanism can be seen from the small number of adults that develop from nymphs. IAC-100/Kaba-8 and IAC-100/Kaba-14 showed a high degree of antibiosis. In addition, the results of field experiment showed that Gema, IAC-100/Kaba-14, and Tanggamus/Pangrango- 78 demonstrated a tolerance to whiteflies. It is shown on a slightly decreasing in yield of these three genotypes (17.33, 19.31, and 19.85%, respectively).